2016
DOI: 10.1179/1942787515y.0000000012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stairway width on pedestrian flow characteristics at railway stations

Abstract: The overall efficiency of transit operation depends on effective operation of various facilities like transit units, transfer stations and access infrastructure. Stairways at transit stations are vital links between different interconnected elements like platforms and foot over bridges. Transfer rate of pedestrians through stairway primarily depends on its geometric design. Many previous studies have reported that the stairway dimensions such as stair gradient, height of riser and length of stairway influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Similar studies over stairways were conducted in India by [72,75,76,78] at inter modal transfer terminals and train stations. All basic flow parameters were measured, and the Figure 9 Speed-density relationships for ascending and descending stairways reported in different studies different regime approaches were defined.…”
Section: Stairway and Escalator Facilitymentioning
confidence: 59%
See 4 more Smart Citations
“…Similar studies over stairways were conducted in India by [72,75,76,78] at inter modal transfer terminals and train stations. All basic flow parameters were measured, and the Figure 9 Speed-density relationships for ascending and descending stairways reported in different studies different regime approaches were defined.…”
Section: Stairway and Escalator Facilitymentioning
confidence: 59%
“…Earlier studies by [68,69,71] over stairways showed that only the age and gender factors were observed to affect the pedestrian speed, but in later studies by [77][78][79][80] the dimension of the stairway (i.e. riser dimension and stairway inclination) and direction of the movement (ascending and descending) were also found to play significant role in determining the movement characteristics of pedestrian over the stairways.…”
Section: Pedestrian Flow Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations